2002
DOI: 10.1055/s-2002-35761
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung eines klinischen Protokolls bei der Behandlung der schweren akuten Pankreatitis

Abstract: Timely recognition and complex therapy of SAP including ICU monitoring, colloids, antibacterial prophylaxis, early enteral nutrition, and CVVHF is the most effective way how to manage this category of patients. Implementation of a specialised treatment protocol considerably improves outcome and reduces the number of deaths associated with surgery and early SAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The mortality rate in AP is influenced by many factors with various degrees including age, etiology, the extent of necrosis, and presence of multi-organ failure [9-10]. Patients managed according to standard guidelines/protocols have shown better outcome in term of complications rate, length of hospital stay, morbidity and mortality [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate in AP is influenced by many factors with various degrees including age, etiology, the extent of necrosis, and presence of multi-organ failure [9-10]. Patients managed according to standard guidelines/protocols have shown better outcome in term of complications rate, length of hospital stay, morbidity and mortality [11].…”
Section: Discussionmentioning
confidence: 99%
“…There are many barriers which can lead to poor adherence to standard guidelines including physicians lack of knowledge and lack of clinical decision support tools. It has been shown that there were better clinical outcomes with increased adherence to guidelines after educating physicians and the introduction of clinical decision support tools in managing patients with AP [11-12]. It is very important that residents and physicians must have a good fund of knowledge about current guidelines for managing AP.…”
Section: Discussionmentioning
confidence: 99%
“…[15] A previous study reported improvements concerning complications, duration of hospital stay, and morbidity and mortality rates of patients followed and treated according to the standard guidelines or protocols. [16] There are many obstacles, including the lack of knowledge of surgeons and the lack of clinical decision support tools, which may lead to non-compliance or poor compliance with standard guidelines. Despite all the barriers, training of major physicians and better definition of clinical decision support tools have resulted in tighter adherence to the guidelines and better clinical outcomes during the management of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the barriers, training of major physicians and better definition of clinical decision support tools have resulted in tighter adherence to the guidelines and better clinical outcomes during the management of acute pancreatitis. [15,16] A similar survey study, which addressed the lack of knowledge of physicians, was conducted with internal medicine and surgical physicians at Abington Jefferson Health; however, the proportion of surgical physicians was relatively low. [17] We should note that similar results in our study indicated a lack of knowledge among the physicians.…”
Section: Discussionmentioning
confidence: 99%